The Smicronychini of southern Africa (Coleoptera, Curculionidae): Review of the tribe and description of 12 new species - Haran, Julien M. (European Journal of Taxonomy, 2021)
This study reviews the species of the tribe Smicronychini Seidlitz, 1891 found in southern Africa. In total, 18 species are recognized in this region, 12 of them being described as new (Sharpia madibai sp. nov., Afrosmicronyx cycnii sp. nov., A. louwi sp. nov., A. marshalli sp. nov., A. nebulosipennis sp. nov., Smicronyx pseudocoecus sp. nov., S. australis sp. nov., S. drakensbergensis sp. nov., S. gracilipes sp. nov., S. paucisquamis sp. nov., S. san sp. nov., S. similis sp. nov.). The following genera and species are newly reported from this area: Afrosmicronyx Hustache, 1935; Sharpia Tournier, 1873; Smicronyx pauperculus Wollaston, 1864; S. albosquamosus Wollaston, 1854 and S. namibicus Haran, 2018. New host plant taxa and plant associations for the tribe are reported among the families Gentianaceae Juss., Orobanchaceae Vent. and Convolvulaceae Juss. A key to species and images of the habitus of adults and male genitalia are provided.